Burn analysis in adult patients hospitalized in the East Centre of Burn Treatment and Reconstructive Surgery in Łęczna - Maja Chrzanowska-Wąsik; Ewa Chemperek; Dawid Sokołowski; Mariusz Goniewicz; Kamil Badnarz; Patryk Rzońca (Kazimierz Wielki University, 2017)
Introduction: Burns are one of the most serious body injuries, which are most frequently sustained by children and older people. In Poland the morality of burn victims is decreasing due to the development of specialized burn treatment centres. Despite huge financial resources and human capital invested in the organization of burn treatment system, the hospitalization time is still long due to the specificity of injuries and their treatment. Material and methods: Records of the adult patients being burn victims hospitalized in the East Centre of Burn Treatment and Reconstructive Surgery in Łęczna were analysed. The analysed data were collected within the period of two years (01.01.2013 - 31.12.2014). Results: Over 70% out of 538 people admitted to the East Centre of Burn Treatment and Reconstructive Surgery in Łęczna were victims of the third-degree burns, among them (over 70%) were men. The average hospitalization time was 21 days and it was longer the higher was the degree of the burns. The depth of burns and body surface area affected by the burns also caused longer hospitalization time. Conclusions: Burn victims are most frequently adult men. Parts of the upper body are most frequently affected by burns. The basic factors determining the survival of the patients are supporting bodily functions after the injury and fast implementation of specialized treatment plan.